The effect of polyamide PA12 and polyester PBT blocks’ lengths on the structure and propertries of multiblock terpoly(amide-block-ester-block-amide) (TPAEA) - Ukielski, R.; Piątek, M. (Polimery, 2022)
The ternary multiblock system terpoly(amide-b-ester-b-amide) (TPAEA) of the chemical structure: poly[(oligoamide-6.36)-block-(tetramethylene terephthalate)-block-laurolactam)] -(PA6.36-b-PBT-b-PA12)n- has been obtained (Table 1). In this system the third component (PBT block here), characterized with the proper molecular weight, is dissolved in hard phase of PA12 blocks and partially dissolved in soft phase of PA6.36. The effects of PA12 and PBT blocks’ lengths on TPAEA properties were investigated. The structure and phase separation were qualitatively estimated on the basis of DSC, DMTA and WAXS results (Fig. 1- 3). It was found that the composition of terpolymer and parts of the blocks determines many TPAEA features and first of all determines its high flexible properties, typical for thermoplastic elastomers (Table 2). It has been proved that PBT as a third component introduced into binary system (multiblock copolymer) in some conditions stabilized the structure acting as a compatibilizer at the domain - matrix border.